The Effect Of Peer Group Conformity On Students` Smoking Behaviorat SMKN 1 Payakumbuh - Rosi Dian Syafitri; Yeni Afrida; Elviana Elviana; Sri Hartati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The purpose of this study was to determine the level of peer group conformity in male students, to determine the level of smoking behavior in male students and to determine how much influence peer group conformity has on smoking behavior in male students at SMKN 1 PayakumbuH. A quantitative regression approach was used in this study. The number of students in the research group was 167 people. The sampling technique used in this study was a simple random sampling technique, namely selecting samples randomly, in this sample using the slovin method with a confidence level of 10%, resulting in a sample of 63 samples. This study used an instrument in the form of data regarding peer group conformity and smoking behavior. To evaluate the research hypothesis, data analysis techniques such as simple linear regression were used. The results of the study showed that: with a percentage level of 51.1% and a significant value of 0.000 <0.05. Thus, it can be concluded that peer group conformity influences smoking behavior..